1994
DOI: 10.1128/jb.176.16.4865-4874.1994
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of the NADP-linked 7 alpha-hydroxysteroid dehydrogenase gene from Clostridium sordellii

Abstract: A bile acid-inducible NADP-linked 7a-hydroxysteroid dehydrogenase (7a-HSDH) from Clostridium sordellii ATCC 9714 was purified 310-fold by ion-exchange, gel filtration, and dye-ligand affinity chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…C. scindens and E. coli constitutively express 7a-HSDHs and are noninducible (69,85). Unexpectedly, the nonsubstrate DCA can induce 7a-HSDH expression in C. absonum and C. sordellii, although the reason for this induction remains unclear (70,76). Macdonald, White, and Hylemon (82) observed the expression of five soluble and two membrane polypeptides upon exposure of C. absonum to DCA and CDCA in the culture medium, although the functions of these additional polypeptides have not been determined.…”
Section: Microbial Bile Acid Hydroxysteroid Dehydrogenase(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…C. scindens and E. coli constitutively express 7a-HSDHs and are noninducible (69,85). Unexpectedly, the nonsubstrate DCA can induce 7a-HSDH expression in C. absonum and C. sordellii, although the reason for this induction remains unclear (70,76). Macdonald, White, and Hylemon (82) observed the expression of five soluble and two membrane polypeptides upon exposure of C. absonum to DCA and CDCA in the culture medium, although the functions of these additional polypeptides have not been determined.…”
Section: Microbial Bile Acid Hydroxysteroid Dehydrogenase(s)mentioning
confidence: 99%
“…7a/b-HSDHs are widespread among the bacteroides and clostridia as well as in E. coli and Ruminococcus species (Table 2) (54,64,(69)(70)(71)(72)(73)(74). In addition, several intestinal clostridia express both 7a-and 7b-HSDHs and have been shown to epimerize the 7a/b-hydroxy group (75,(76)(77)(78).…”
Section: Microbial Bile Acid Hydroxysteroid Dehydrogenase(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…The investigators reported that the addition of taurocholate to cecal contents from mice that had not been treated with antibiotics yielded substances that were inhibitory to C. difficile growth, while taurocholate-supplemented cecal contents from antibiotic treated mice were permissive for C. difficile growth. The authors also determined that the cecal microbiota were metabolizing taurocholate into secondary bile salts that were inhibitory for C. difficile growth, and that the presence of the enzymes responsible for converting primary bile salts into secondary bile salts were found in equivalent concentrations in both the cecum and in the feces ( Coleman et al, 1994;Berr et al, 1996;Thomas et al, 2001), an observation recently supported by meta-metabolomic profiling (Theriot et al, 2014). A recent report by Howerton et al (2013) described the use of a synthetic derivative of taurocholate, CamSA, which is a competitive inhibitor of taurocholate-induced spore germination that protected mice from challenge with a large number of C. difficile spores, further implicating the critical role of bile salts in the regulation of spore germination.…”
Section: Discussionmentioning
confidence: 99%